Review of clinical and imaging findings in autoimmune glial fibrillary acidic protein astrocytopathy to aid in early diagnosis - Li, Xiaomeng; Li, Jiacun; Xu, Han; Liu, Xiaohui; Li, Meilin; He, Jingzhen; Xiu, Jianjun (Frontiers in Immunology, 2024)
ObjectiveAutoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) is a novel steroid sensitive autoimmune disease, without a diagnostic consensus. The purpose of this study was to improve early GFAP-A diagnosis by increasing awareness of key clinical characteristics and imaging manifestations.MethodsMedical records of 13 patients with anti-GFAP antibodies in serum or cerebrospinal fluid (CSF) were reviewed for cross-sectional and longitudinal analysis of clinical and magnetic resonance imaging (MRI) findings.ResultsThe predominant GFAP-A clinical manifestations are limb weakness/numbness and fever. GFAP-A has a propensity in the early stage for meningeal and leptomeningeal lesions on the brainstem surface, with a typical pattern of periventricular linear radial and leptomeningeal enhancement. The clinical manifestations and leptomeningeal enhancement were rapidly alleviated after treatment with high doses of corticosteroids or/and intravenous immunoglobulin, although, there are patients who may present with increased brain parenchymal lesions. On 3T MRI, the spinal cord demonstrated extensive longitudinal T2-weighted hyper-intensity, central distribution, and gray matter involvement. Optic nerve involvement in some patients was also noted with optic nerve swelling and abnormal enhancement. In addition to the classic reversible splenium of corpus callosum syndrome (type I), this study found the much rarer type II with diffusion restriction on DWI (Diffusion Weighted Imaging) in the corpus callosum. Positive anti-GFAP antibodies in serum or cerebrospinal fluid (CSF) are important for GFAP-A diagnosis with overlapping antibodies commonly noted. This study found anti-GM3 antibodies, a rare finding also previously reported.ConclusionThis study correlates GFAP-A clinical and imaging features, noting a “delay” phenomenon between clinical manifestations, treatment response, and radiographic MRI findings. MRI T2-FLAIR brainstem hyperintensity and T2-FLAIR gadolinium enhanced images, and subtraction techniques were valuable for early lesion detection and accurate diagnosis.